The housing market and agricultural land dynamics: Appraising with Economic Policy Uncertainty Index - Alola, Andrew Adewale; Uzuner, Gizem (Wiley, 2020)
Agricultural land is a main component of the environment and ecological system. Therefore, this study employs the panel cointegration approach to investigate the dynamic relationship between the housing market vis-a-vis housing price (hp) and agricultural land (land) of a panel of 15 countries (countries with the gross domestic product-weighted average of the national Economic Policy Uncertainty index) over the period 1997-2015. Additionally, Granger causality approach of Dumitrescu-Hurlin is employed for the investigation. The model adjusts to the long-run equilibrium with an annual speed of 11% from any situation of disequilibrium and with elasticities of -3.97 and -0.67, respectively, for a land and Global Economic Policy Uncertainty (gepu). Meanwhile, the impact during a short run of gepu is statistically significant and positive on hp, whereas it is not significant for land. Interestingly, the investigation reveals Granger causality from agricultural land to the housing price with feedback. The research presents an indication that policymaker(s) and urbanization stakeholders should be more concern about effective and sustainable long-term policies. Future anomalies of food scarcity and skyrocketing house prices associated with agricultural land-house price trade-off challenges could potentially be mitigated by such effective policy frameworks.
Keywords: agricultural land; global economic policy uncertainty; housing prices